Impact of Social Media on Electoral Politics: Recent Trends: Examining the influence of social media on electoral politics (Journal of Advances and Scholarly Researches in Allied Education, 2018)
There is extensive worry about the job of social media, for example, Face book and Twitter, play in advancing observations during political crusades. These advancements are broadly utilized, and data streaming crosswise over them has a prominent. This exploration recognizes the on-going patterns on Impact of social media on Electoral politics.